Al-Farra' dan Nahwu Mazhab Kufah - Muhammad Sayyid An Nabiil; Mukhamad Sarifudin (STAI Masjid Syuhada Yogyakarta, 2024)
Kufah and Bashrah are cities that have become centers of intellectual development. Initially, the progress in Bashrah was faster because it was closer to the seat of power. Meanwhile, in Kufah, the initial progress in knowledge focused on qiraat, the transmission of poetry, fiqh, and nahwu (grammar). Despite this, the scholars of the Kufah school had a distinctive method, which was completely different from that of Bashrah. Due to these differences, their presence in the field of nahwu scholarship is considered a distinct school of thought. This research is a literature-based study, utilizing a qualitative descriptive research method. The emphasis of this research is on the thoughts of Al Fara', who is one of the scholars of the Kufah school. The purpose of this research is to understand the characteristics of Al Fara''s nahwu thinking that differentiate it from the Bashrah school. The results of this research reveal differences between the Kufah and Bashrah schools in their flexibility in dealing with linguistic phenomena. This difference is most apparent in the contrasting approaches of two prominent figures, Al-Kisa'i and Al-Farra'. However, these distinct characteristics reach their peak in the hands of Al-Farra', who contributes new terms to the field of nahwu. Keywords: Al Fara’, Grammar Science, Kufa School of Thought, Basra School of Thought